Mitochondria: their role in spermatozoa and in male infertility. (8th February 2021) - Boguenet, Magalie; Bouet, Pierre-Emmanuel; Spiers, Andrew; Reynier, Pascal; May-Panloup, Pascale
Abstract: BACKGROUND: The best-known role of spermatozoa is to fertilize the oocyte and to transmit the paternal genome to offspring. These highly specialized cells have a unique structure consisting of all the elements absolutely necessary to each stage of fertilization and to embryonic development. Mature spermatozoa are made up of a head with the nucleus, a neck, and a flagellum that allows motility and that contains a midpiece with a mitochondrial helix. Mitochondria are central to cellular energy production but they also have various other functions. Although mitochondria are recognized as essential to spermatozoa, their exact pathophysiological role and their functioning are complex. Available literature relative to mitochondria in spermatozoa is dense and contradictory in some cases. Furthermore, mitochondria are only indirectly involved in cytoplasmic heredity as their DNA, the paternal mitochondrial DNA, is not transmitted to descendants. OBJECTIVE AND RATIONAL: This review aims to summarize available literature on mitochondria in spermatozoa, and, in particular, that with respect to humans, with the perspective of better understanding the anomalies that could be implicated in male infertility. SEARCH METHODS: PubMed was used to search the MEDLINE database for peer-reviewed original articles and reviews pertaining to human spermatozoa and mitochondria. Searches were performed using keywords belonging to three groups: 'mitochondria' or 'mitochondrial DNA', 'spermatozoa' or 'sperm' and 'reactive oxygen species' or 'calcium' or 'apoptosis' or signaling pathways'. These keywords were combined with other relevant search phrases. References from these articles were used to obtain additional articles. OUTCOMES: Mitochondria are central to the metabolism of spermatozoa and they are implicated in energy production, redox equilibrium and calcium regulation, as well as apoptotic pathways, all of which are necessary for flagellar motility, capacitation, acrosome reaction and gametic fusion. In numerous cases, alterations in one of the aforementioned functions could be linked to a decline in sperm quality and/or infertility. The link between the mitochondrial genome and the quality of spermatozoa appears to be more complex. Although the quantity of mtDNA, and the existence of large-scale deletions therein, are inversely correlated to sperm quality, the effects of mutations seem to be heterogeneous and particularly related to their pathogenicity. WIDER IMPLICATIONS: The importance of the role of mitochondria in reproduction, and particularly in gamete quality, has recently emerged following numerous publications. Better understanding of male infertility is of great interest in the current context where a significant decline in sperm quality has been observed.